Assessment of Acute and Chronic Pharmacological Effects on Energy Expenditure and Macronutrient Oxidation in Humans: Responses to Ephedrine - Antonella Napolitano; Peter R. Murgatroyd; Nick Finer; Elizabeth K. Hussey; Robert Dobbins; Steve O'Rahilly; Derek J. R. Nunez (Journal of Obesity)
Evidence of active brown adipose tissue in human adults suggests that this may become a pharmacological target to induce negative energy balance. We have explored whole-body indirect calorimetry to detect the metabolic effects of thermogenic drugs through administration of ephedrine hydrochloride and have assessed ephedrine's merits as a comparator compound in the evaluation of novel thermogenic agents. Volunteers randomly given ephedrine hydrochloride 15 mg QID (n=8) or placebo (n=6) were studied at baseline and after 1-2 and 14-15 days of treatment. We demonstrate that overnight or 23-hour, 2% energy expenditure (EE) and 5% fat (FO) or CHO oxidation effects are detectable both acutely and over 14 days. Compared to placebo, ephedrine increased EE and FO rates overnight (EE 63 kJ day 2, EE 105 kJ, FO 190 kJ, day 14), but not over 23 h. We conclude that modest energy expenditure and fat oxidation responses to pharmacological interventions can be confidently detected by calorimetry in small groups. Ephedrine should provide reliable data against which to compare novel thermogenic compounds.